Islamic modes of finance and Islamic financial intermediation in the selected 8 OIC countries - Maamor, Selamah; Abdullah, Hussin (American Scientific Publishers, 2015)
The importance of Islamic modes of finance in financial inter mediation has been emphasized in recent research.Islamic modes of finance are designed to facilitate financing by the principles in Islamic Sharia, such as mudārabah, mushāraka and sukuk.Islamic modes of finance do not only act an indicator in financial inter mediation, but it also contributes to economic growth.The objective of this study is to determine the relationship between Islamic modes of finance and Islamic financial inter mediation of selected 8 OIC member countries.This study employed fixed effect and random effect through panel data of 8 OIC countries over the period of 2000–2012.Findings show that Islamic mode of finance and liquid liabilities have positive and significant effects to financial inter mediation.While, quasi money does not affect Islamic financial inter mediation.